Artificial Intelligence Annual Volume 2022 - Antonio Aceves Fernandez, Marco; Travieso-Gonzalez, Carlos M. (Artificial Intelligence, 2022)
Artificial Intelligence (AI) has attracted the attention of many researchers and users alike, and it has become increasingly crucial in our modern society. From cars, smartphones, airplanes, medical equipment, consumer applications, and industrial machines, among others, the impact of AI is notoriously changing the world we live in and making it better in many areas. However, it is equally important to remember that every progress comes with certain challenges that we as a society must address.